2003
DOI: 10.1207/s15374424jccp3203_04
|View full text |Cite
|
Sign up to set email alerts
|

Children's Classroom Peer Relationships and Subsequent Educational Outcomes

Abstract: Used children's peer relationships (social preference, aggression, and withdrawal) to predict educational outcomes in a 10-year longitudinal study of 524 students in Grades 3 to 5. Consistent with prior research, lower social preference and elevated aggression and withdrawal were each associated with lower graduation rates; however, only aggression uniquely predicted outcomes. Ethnicity and socioeconomic status (SES) predicted educational outcomes and moderated the association between peer acceptance and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 24 publications
3
60
1
4
Order By: Relevance
“…Children demonstrating early academic and learning difficulties are not only more likely to display later academic difficulties including school drop-out (Horn & Packard, 1985), but they are also at risk for developing later peer rejection (Ladd, 1990;Risi, Gerhardstein, & Kistner, 2003) as well as emotional and behavioral disorders including conduct disorder (Bennett, Brown, Boyle, Racine, & Offord, 2003; Moffit, Gabrielli, Mednick, & Schulsinger, 1981). Given these negative outcomes as well as the consistent finding that academic success tends to be stable after first grade (Entwisle & Hayduk, 1988), researchers have attempted to examine sociocultural, school, family, and individual factors that contribute to a child's early school Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: The Role Of Emotion Regulation In Children's Early Academic mentioning
confidence: 99%
See 1 more Smart Citation
“…Children demonstrating early academic and learning difficulties are not only more likely to display later academic difficulties including school drop-out (Horn & Packard, 1985), but they are also at risk for developing later peer rejection (Ladd, 1990;Risi, Gerhardstein, & Kistner, 2003) as well as emotional and behavioral disorders including conduct disorder (Bennett, Brown, Boyle, Racine, & Offord, 2003; Moffit, Gabrielli, Mednick, & Schulsinger, 1981). Given these negative outcomes as well as the consistent finding that academic success tends to be stable after first grade (Entwisle & Hayduk, 1988), researchers have attempted to examine sociocultural, school, family, and individual factors that contribute to a child's early school Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: The Role Of Emotion Regulation In Children's Early Academic mentioning
confidence: 99%
“…One mechanism by which children's emotion regulation skills may contribute to their early academic success is through behavioral control in the classroom. A number of studies have indeed found that adolescents with deficits in behavioral control-such as those with externalizing problems including aggression and antisocial behavior-are more likely to have both co-occurring (Al Otaiba & Fuchs, 2002;Malecki and Elliot, 2002;Wentzel, 1993) and later academic difficulties (Masten et al, 2005;Risi, Gerhardstein, & Kistner, 2003). These observed deficits in behavioral control negatively impact the student's ability to attend to information presented by teachers as well as complete school related tasks or assignments that foster learning (Kuhl & Kraska, 1989).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…However, the role of friends and classmates in the school adjustment process has been given less attention than the role of parents and teachers (Risi, Gerhardstein, and Kisner 2003;Rubin, Bukowski, and Parker 1998;Ryan, Stiller, and Lynch 1994;Ryan 2000). Few researchers have investigated peer relations between adolescence and adulthood (Berndt and Murphy 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Obsuth and colleagues (2016) linked their findings to the SDM's (Hawkins, 1999) proposition that youth who develop close attachments to their teachers are motivated to behave in a prosocial manner, consistent with the teachers' professional school-based values and conduct. In contrast, other research has shown that school-based peer relations foremost shape students' school experience (Cullingford & Morrison, 1997;Risi, Gerhardstein, & Kistner, 2003).…”
Section: Schoolmentioning
confidence: 80%
“…In other words, the young person can actively disrupt the social bonds. For example, research shows that aggressive children can jeopardise their prosocial relations through aggressive behaviours (Adams, Bukowski, & Bagwell, 2005;Dodge, Coie, & Lynam, 2006;Risi et al, 2003). In Isaac's case, his relapse into antisocial behaviour changes how his parents respond to him.…”
Section: Isaac's School Engagementmentioning
confidence: 99%